2022
DOI: 10.1111/nyas.14746
|View full text |Cite
|
Sign up to set email alerts
|

Mediating factors of statistics anxiety in university students: a systematic review and meta‐analysis

Abstract: Statistics play a key role in many areas of modern society including technology, social and behaviour studies, economics and the sciences. Statistics anxiety (SA) has a detrimental impact on academic experiences in university populations. Although, the mediator factors remain underexplored. We conducted the first systematic review and meta-analysis focused on SA in university students in the context of: statistical performance; individual differences in statistical learning; self-perceptions regarding statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 73 publications
(283 reference statements)
1
16
0
Order By: Relevance
“…This issue has also been addressed globally by the World Health Organization [10] and specifically with the Italian population [12]. It is crucial to note that our observations on the coping strategies of Italian students and their relationships with school anxiety are supported by previous studies [14]. We agree with Lazarus and Folkman [15] that coping strategies can be considered as responses to stress beyond individual capabilities.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This issue has also been addressed globally by the World Health Organization [10] and specifically with the Italian population [12]. It is crucial to note that our observations on the coping strategies of Italian students and their relationships with school anxiety are supported by previous studies [14]. We agree with Lazarus and Folkman [15] that coping strategies can be considered as responses to stress beyond individual capabilities.…”
Section: Discussionsupporting
confidence: 84%
“…Likewise, the coping strategies implemented by Italian students exert a direct impact on their levels of school anxiety [14]. Coping strategies are defined as the cognitive and behavioral efforts that individuals employ to manage internal and external demands that are perceived as exceeding their resources [15].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, differences between MA measurement instruments should be accounted for when investigating links between MA and mathematics performance 30 . The difference between MA and statistics anxiety, a topic that has gained interest in recent years, 31–33 is also essential to distinguish; in particular, the similarity of items measuring these two constructs necessitates further study to clarify how they are related. Among the findings are gender differences in MA and statistics anxiety, which are not as consistently found for the latter 34,35 .…”
Section: Blank Spots and The Future Research Agendamentioning
confidence: 99%
“…However, there is also evidence to suggest there is no significant link between statistics anxiety and examination performance [ 12 ]. The overall evidence is equivocal and a recent review concluded that the inconclusive evidence may be a consequence of cognitive and individual differences (e.g., procrastination: [ 13 ]). Nevertheless, it is plausible that statistics anxiety contributes to reduced academic performance, but the relationship may not be simple, linear, or constant over time [ 10 , 14 ]; warranting further investigation.…”
Section: Introductionmentioning
confidence: 99%